2003
DOI: 10.1108/14626000310473166
|View full text |Cite
|
Sign up to set email alerts
|

Which advisers do micro‐firms use? Some Australian evidence

Abstract: Despite the growth of many new business advice and support services over the last 15 years, the extent to which such facilities are used by the Australian small business sector has not been extensively examined, especially amongst the micro‐enterprises that comprise the majority of all small firms. Home based businesses (HBBs) constitute the largest group of micro‐businesses in Australia, as well as comprising the biggest single SME sector in the nation. An investigation into the usage of advisory services by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 9 publications
4
64
0
3
Order By: Relevance
“…However, the above study does not measure the awareness of respondents pertaining to business advisory services. A similar study in Australia indicated that government support programmes were not the main choice for SMEs (Jay and Schaper, 2003). The utilisation rate on the services provided was far beyond satisfactory.…”
Section: Micro-sized Business Awareness Of Advisory Servicesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, the above study does not measure the awareness of respondents pertaining to business advisory services. A similar study in Australia indicated that government support programmes were not the main choice for SMEs (Jay and Schaper, 2003). The utilisation rate on the services provided was far beyond satisfactory.…”
Section: Micro-sized Business Awareness Of Advisory Servicesmentioning
confidence: 97%
“…The study by Morales and Marquina (2008) also shows that age of employees was not significantly vary with the perception team performance. However, in terms of utilisation of business advisory, a study by Jay and Schaper (2003), shows that the older of the age the more the owner seeks the advice from those who knowledgeable in business. Both studies disclosed a contradiction of the two different views of advisorybetween utilisation of advice and firms performance vis-a-vis to age of the management.…”
Section: Micro-sized Business Awareness Of Advisory Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Les facteurs de satisfaction des PME à l'égard de leurs banques concernent les interactions interpersonnelles (O'Donnell, Durkin et McCartan-Quinn, 2002), la personnalisation des rapports (Gill, Flaschner et Shachar, 2006), la gestion des comptes, les politiques et les procédures relatives à la relation banque/PME (Madill et al, 2002), les charges et les frais (Ibbotson et Moran, 2003), la confiance (Howorth et Moro, 2006 ;Hernández-Cánovas et Martínez-Solano, 2010). Certains auteurs évoquent le rôle de conseil (Jay et Schaper, 2003) et d'intermédiaire lors du PAPÉ (Kutsuna, Smith et Smith, 2007). En somme, il apparaît que les petites banques sont plus performantes dans leurs relations avec les Revue internationale P.M.E., vol.…”
Section: Le Financement Bancaireunclassified
“…7, No. 16; few programs that have been able to penetrate the market, the government support programs are generally unpopular among SMEs (Berry, et al, 2006;Jay & Schaper, 2003) Foziah et al, 2006). Here, the high level of bureaucracy and stringent terms and conditions has often been identified as a factor discouraging SMEs from dealing with GBSS (Abdul Aziz & Faoziah, 2009;Hakimin, 2010;Khairudin, 2007;Salleh & Ndubisi, 2006).…”
Section: Research Problemmentioning
confidence: 99%